2017
DOI: 10.4309/jgi.2017.35.4
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Issue of Problem Gambling in the Criminal Justice System: A Series of Case Studies

Abstract: The prevalence rates of problem gambling in the adult correctional population are 5 to 10 times higher than those found in the general population. Yet little has been published about dealing with problem gamblers in correctional settings. We conducted a literature review and interviewed 16 key informants who provide services to clients experiencing problem gambling and/or who have worked in the criminal justice system. Our objective was to gain greater understanding of programming for problem gambling for clie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The Amherst Gambling Treatment Court in New York State stands as a pioneering model for any court interested in establishing a gambling court to permit a defendant to enter a gambling diversion treatment program if a criminal judge deems, they are eligible instead of incarceration (Cohen et al, 2013). Together with the Nevada Eighth Judicial District Court and a handful of other legal bodies, specialty courts are an effective way to address root-causes that lead to recidivism (Turner et al, 2017). The Nevada program has been considered as a gold-standard for gambling addiction reform and treatment, and courts from around the US have expressed interest in modeling similar programs.…”
Section: Discussionmentioning
confidence: 99%
“…The Amherst Gambling Treatment Court in New York State stands as a pioneering model for any court interested in establishing a gambling court to permit a defendant to enter a gambling diversion treatment program if a criminal judge deems, they are eligible instead of incarceration (Cohen et al, 2013). Together with the Nevada Eighth Judicial District Court and a handful of other legal bodies, specialty courts are an effective way to address root-causes that lead to recidivism (Turner et al, 2017). The Nevada program has been considered as a gold-standard for gambling addiction reform and treatment, and courts from around the US have expressed interest in modeling similar programs.…”
Section: Discussionmentioning
confidence: 99%
“…The welfare state and its justice system could well benefit from the introduction of gambling courts, for example (see e.g. Hinshaw 2005;Guenaga 2011;Turner et al 2017;Laux 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Both the connection between gambling and crime and that between gambling and social disadvantage are well established. Numerous studies have found higher rates of problem gambling among criminal offenders than in the general population (Turner and McAvoy 2011;May-Chahal et al 2017;Turner et al 2017;Moore 2018;Riley et al 2018;Lind et al 2019;Widinghoff et al 2019;Banks et al 2020). Although only a relatively small proportion of all crime is gambling-related (Arthur et al 2014), a study on British prisoners estimated that problem gambling is linked with up to 13% of all offending (May-Chahal et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals entering the Canadian correctional systems currently undergo a battery of questionnaires at intake to assess their risk, need, and responsivity (RNR) (Andrews et al, 1986;Bonta & Andrews, 2007;Bourgon & Armstrong, 2005;Motiuk, 1997), but none of these tools assess problem gambling as either a direct or indirect risk factor. In a recent qualitative study, Turner et al (2017) used key expert interviews to describe the breadth of treatment programs that have been implemented in Canada and the United States, and while a small number of programs were identified, there are remarkably few programs set up to help people in the correctional system overcome a gambling disorder (Turner et al, 2017). The vast majority of people experiencing a gambling disorder have no access to treatment or programming services to deal with their gambling problem while incarcerated.…”
Section: Introductionmentioning
confidence: 99%
“…The limited number of correctional treatment programs for people experiencing problem gambling has been accompanied by a notable lack of evidence-based research evaluating the effectiveness of the programs that do exist (Perrone et al, 2013;Turner et al, 2017). Perrone et al (2013) note that within the correctional environment, problem gambling treatment services remain largely undocumented and unevaluated.…”
Section: Introductionmentioning
confidence: 99%